2015
DOI: 10.1002/jcla.21842
|View full text |Cite
|
Sign up to set email alerts
|

CD235a (Glycophorin‐A) Is the Most Predictive Value Among Different Circulating Cellular Microparticles in Thrombocytopenic Human Immunodeficiency Virus Type 1

Abstract: Different cellular MPs and platelets activated in HIV patients could have a role in thrombotic events in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…ErMPs have also emerged as potential mediators of transfusion‐related morbidity by thrombin‐dependent activation of the complement system . Moreover, CD235a + ErMPs are sensitive predictors of thrombotic events in thrombocytopenic HIV patients . However, the physiologic role of ErMPs has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…ErMPs have also emerged as potential mediators of transfusion‐related morbidity by thrombin‐dependent activation of the complement system . Moreover, CD235a + ErMPs are sensitive predictors of thrombotic events in thrombocytopenic HIV patients . However, the physiologic role of ErMPs has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Thus, an intense and persistent activation of platelets/microparticles can contribute to increased vascular risks which underlie HIV-associated endothelial dysfunction with thrombotic events and vascular diseases. (18,19,20) Therefore, our findings emphasise that an increased oxidative stress in platelets and P-MPs may increase the risk of RF during HIV-TB coinfection.…”
Section: Proof Proof Proofmentioning
confidence: 64%
“…The TF on PEVs could originate from the platelet or its uptake from TF-bearing EVs of other cellular origins [ 132 ]. Alternatively, PEVs can affect coagulation through the activation of other cells to induce a pro-thrombotic environment [ 53 , 57 , 58 , 103 , 105 , 120 , 121 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ] ( Figure 5 ). As an example, Terrisse et al found that PEVs will adhere to endothelial cells dependent on lactadherin, PS, and αVβ3 integrin.…”
Section: Platelet-derived Extracellular Vesicles Under Disease Condit...mentioning
confidence: 99%
“…HIV Tat1 directly activates platelets through chemokine receptor 3 (CCR3) and β3-integrin, resulting in PEV formation [ 191 ]. Correspondingly, patients with HIV have increased numbers of PEVs in their blood [ 9 , 58 , 76 , 192 ], though the numbers of PEVs detected are again variable in different reports. Hijmans et al found 40 PEVs per µL plasma in healthy individuals and 140 PEVs per µL plasma in HIV patients [ 76 ], while Falasca et al found 897 annexin V negative and 112 annexin V positive PEVs per µL plasma in healthy individuals and 1419 annexin V negative and 215 annexin V positive PEVs per µL plasma in HIV patients [ 192 ].…”
Section: Platelet-derived Extracellular Vesicles In Infectious Diseasesmentioning
confidence: 99%